Applying new methodological tools in human rights research. The case of qualitative comparative analysis. Issue 3 (2nd April 2016) - Marx, Axel; Soares, Jadir
Abstract : In recent years several excellent efforts have been made to explain the protection of human rights on the basis of quantitative regression-based models. These studies have generated several interesting insights and identified different explanatory variables which explain the protection of human rights. However, regression-based models have some limitations due to the assumptions on which they are based. Most importantly these models aim to identify the 'net' additive effect of individual explanatory variables, neglecting the fact that these variables can have different effects depending on the interaction with other variables. Recently, a new set of analytic techniques, set theoretic qualitative comparative analysis (QCA), have emerged which are based on a different set of assumptions and which are able to identify more complex explanations. These techniques have a few potentially distinct strengths. First, QCA develops a conception of causality that leaves room for complexity. Second, it is based on Set theory which allows for the identification of (combinations) of necessary and/or sufficient conditions/explanatory variables. Analysing relations between variables in terms of necessity and sufficiency potentially contributes to a more powerful understanding of which factors are key to understand the protection of human rights. This article first provides an assessment of quantitative studies which aim to explain the protection of human rights, operationalised in different ways. This assessment results in an overview of independent and dependent variables and data used in existing studies. In a second part, QCA as a methodological technique is introduced and its strengths and weaknesses discussed.